Empirical study of the relationship of architectural form details to the state of conservation of modern heritage through damage maps - Kaminski, Matheus Gregorio (2025)
The Sustainable Development Center of the University of Brasilia is one of the modernist buildings that make up the Darcy Ribeiro campus. The architectural project contains several recommendations for the execution of a flat roof waterproofing system, as well as details for rainwater runoff and drainage, which reveals the architect’s concern with watertightness. This research seeks to identify the relationship between the pathological manifestations recognized on the roof and the details of the semicircular shape of the building, assessing the state of conservation using damage maps as an auxiliary analysis tool. This study is based on a field survey using aerophotogrammetry with a drone, the application of vector drawing software for graphic representation and discussion of the possible causes, and the agents and mechanisms of degradation at work. The results show the importance of mechanical protection for the good performance of the waterproofing system, as well as the need for correct sizing of expansion joints to absorb and relieve the stresses caused by hygrothermal variations. The incorporated methodology proved to be effective and economical in diagnosing and monitoring pathological manifestations, making it possible to plan maintenance actions that extend the useful life and preserve the intrinsic characteristics of building systems.